Investigation of the impressed current cathodic protection method for the cable parallel wires in the rainwater electrolyte based on acoustic emission method. (30th December 2019) - Hu, Pengyue; Li, Shengli; Jiang, Nan; Yan, Yadan
Highlights: Apply impressed current cathodic protection to parallel wires. The rainwater used as electrode. Acoustic emission used to study the test method. Abstract: The corrosion durability of bridge cables in operation is prominent. This study proposes an active protection method to apply impressed current cathodic protection (ICCP) to bridge cable parallel wires. The weight loss method, scanning electron microscopy, electrochemical test, and acoustic emission (AE) signal characteristic analysis were used to study the test method for electrochemical corrosion protection of cable parallel wires using rainwater conduction. Results show that cable wires are corroded on the surface and inside, whereas the cable wires with ICCP show different changes. The cable wires are effectively protected in the environment where a sodium chloride solution is used to simulate rainfall. In the AE test of the cable wires after corrosion using a signal generator, the main frequency of the AE signal gradually increases with the increase in corrosion degree. The high corrosion degree of the cable wires induces dispersion. The characteristics of AE signal can reflect the corrosion degree of the cable wires, and ICCP can decrease the corrosion rate of the cable wires.